Global impact of an educational antimicrobial stewardship programme on prescribing practice in a tertiary hospital centre. (20th March 2013) - Cisneros, J. M.; Neth, O.; Gil‐Navarro, M. V.; Lepe, J. A.; Jiménez‐Parrilla, F.; Cordero, E.; Rodríguez‐Hernández, M. J.; Amaya‐Villar, R.; Cano, J.; Gutiérrez‐Pizarraya, A.; García‐Cabrera, E.; Molina, J.; et al.
Abstract The misuse of antibiotics has been related to increased morbidity, mortality and bacterial resistance. The development of antimicrobial stewardship programmes (ASPs) has been encouraged by scientific societies as an essential measure. An educational, institutionally supported ASP was developed in our tertiary‐care centre. Local guidelines on the management of infectious syndromes were created. Antimicrobial prescriptions were chosen arbitrarily weekly and counselling interviews by expert clinicians were carried out, using a paedagogic, non‐restrictive methodology. Satisfaction with the interview was assessed using anonymous questionnaires. The appropriateness of antimicrobial prescriptions as well as consumption was assessed prospectively throughout the year. Feedback regarding the correct use of treatments was communicated to each participating department periodically. The improvement in antimicrobial prescription was included among the annual objectives linked to economic incentives in every department. A total of 1206 counselling interviews were carried out during the first year. Fifty‐three per cent of antimicrobial prescriptions (176/332) were inappropriate when the programme started. The rate of inappropriate prescriptions continuously declined to 26.4% (107/405) in the fourth trimester (p <0.001; RR = 0.38; 95% CI, 0.23–0.43). Antimicrobial consumption decreased from 1150 defined daily doses (DDDs) per 1000 occupied bed‐days in the first trimester to 852 DDDs in the fourth, reflecting a reduction in antimicrobial expenditures of 42%. A total of 352 satisfaction questionnaires were received and 98% described the advice as positive. In conclusion, the implementation of an education‐based ASP achieved a significant improvement in all antimicrobial prescriptions in the centre and a reduction in antimicrobial consumption, even when no restrictive measures were implemented. The programme was highly accepted by all prescribers.